Method of Interpreting the High Resolution Seismic Profiles: Principle and Application in Coastal Shallow Water Area of Red River Delta - Nghi, Tran; Thanh, Dinh Xuan; Thanh Nhan, Tran Thi; Thinh, Tran Trong; Phuong Thao, Nguyen Thi; Dien, Tran Ngoc; Huyen Trang, Nguyen Thi; Ha Vu, Pham Nguyen; Dung, Tran Thi (VNU Journal of Science: Earth and Environmental Sciences; Vol 35 No 2, 2019)
Abstract: Establishing a process of interpreting the high-resolution seismic profile according to a sedimentary geological point of view is a very urgent task. The explanation process can be divided into the following steps: (1) Boundary demarcation of sequences based on unconformable surfaces showing signs of erosion of the river bed; (2) Analysis of lithofacies and lithofacies association according to time and to space in relation to global sea level change; (3) Demarcation of systems tract: low stand systems tract (LST), Transgressive systems tract (TST) and Highstand systems tract (HST). On that basis, Tran Nghi (2012) established an integrated general formula between lithofacies and systems tract: (1) Li LST = arLST + amrLST; (2) Li TST = atTST + amtTST + mtTST; (3) Li HST = ahHST + amhTST Where, Li - Lithofacies; ar - Alluvial facies of lowstand systems tract; at - Alluvial facies of transgressive systems tract; ah - Deltaic facies of lowstand systems tract; amr - Deltaic facies of highstand systems tract; amt- Coastal facies of transgressive systems tract; mt - Shallow sea facies of maximum transgressive systems tract;  The results have determined the exact location of the ancient river channels and their’s change history in the shallow coastal area of ​​the Red River Delta. Before 1787, the ancient Red River channel had the largest scale flowing to the sea through Ha Lan mouth (T22-1), while the river channel flowing into Ba Lat mouth was only a tributary of the Red River (T12). The seismic section of line T22-1 (Ha Lan mouth) allows the determination of the ancient Red River channel and line T12 (Ba Lat mouth) has identified the tributary channel of the Red River. The boundary between lithofacies complexes in vertical seismic section (bottom up) is determined as follows: arLSTQ 1 3b à atTSTQ 2 1 à amt 1 TSTQ 2 1-2 à amt 2 TSTQ 2 1-2 à mtTSTQ 2 2 à amhHSTQ 2 3 . Keywords: Lithofacies, lithfacies association, seismic wave field, systems tract, transgressive alluvial lithofacies (atTST). References : [1] Trần Nghi, Ngô Quang Toàn, Đặc điểm các chu kỳ trầm tích và lịch sử tiến hóa địa chất Đệ tứ đồng bằng Sông Hồng, Tạp chí địa chất A (206-207) (1991) 65-69. [2] Trần Nghi, Trầm tích học (tái bản), Nhà xuất bản Đại học Quốc gia Hà Nội, Hà Nội, 2012. [3] Trần Nghi, Trần Thị Thanh Nhàn, Trần Ngọc Diễn, Đinh Xuân Thành, Trần Thị Dung, Nguyễn Thị Phương Thảo, Trần Xuân Trường, Đỗ Mạnh Tuân, Diễn biến bồi tụ - xói lở bờ biển Thái Bình-Nam Định từ Holocen muộn đến nay trong mối quan hệ với tiến hóa các thùy châu thổ và lịch sử sông Sò, Tạp chí Khoa học, ĐHQGHN 34 (4) (2018). https://doi.org/10.25073/2588-1094/vnuees.4346 [4] Trần Nghi, Nguyễn Thị Tuyến, Đinh Xuân Thành, Nguyễn Đình Nguyên, Trần Thị Thanh Nhàn, Nguyễn Đình Thái, Nguyễn Thị Huyền Trang, Lê Viết Chuẩn, Nguyễn Hoàng Long, Đặc điểm tướng đá – cổ địa lý Pleistocen muộn – Holocen khu vực cửa sông Ba Lạt, Tạp chí Khoa học và Công nghệ Biển 17 (1) (2017) 23-34. https://doi.org/ 10.15625/1859-3097/17/1/8476 [5] Trần Nghi, Nguyễn Thị Tuyến, Đinh Xuân Thành, Nguyễn Đình Nguyên, Trần Thị Thanh Nhàn, Nguyễn Đình Thái, Nguyễn Thị Huyền Trang. Đường bờ cổ và ranh giới chéo các miền hệ thống trầm tích Pleistocen muộn - Holocen khu vực Bắc bộ và Bắc trung bộ. Tạp chí Địa chất A (358) (2016) 1-13. [6] Vũ Cao Minh, Nguyễn Khắc Nghĩa, Nguyễn Huy Thịnh, Biến động cửa Ba Lạt, cửa Hà Lạn trong thời kỳ cận đại và ảnh hưởng của chúng tới diễn biến bồi tụ xói lở khu vực Hải Hậu - Nam Định. Tạp chí KH&CN Thủy lợi Viện KHTLVN 3(13) (2013) 32 - 41. [7] Doãn Đình Lâm, Tiến hóa trầm tích Holocen châu thổ Sông Hồng, Luận án tiến sĩ địa chất, ĐHQGHN, 2003. [8] Tran Nghi, Mai Trong Nhuan, Chu Van Ngoi, Nguyen Van Dai, Dinh Dinh Xuan Thanh, Nguyen Dinh Nguyen, Nguyen Thanh Lan, Dam Quang Minh, Ngo Quang Toan, GIS and image analysis to study the process of late Holocene sedimentary evolution in Balat River Mouth, Vietnam, Geoinformatics 14(1) (2003) 43-48. [9] Tran Nghi, Mai Trong Nhuan, Chu Van Ngoi, P. Hoekstra, Utrecht, TJ. Van Weering, J.H. Van Denbergh, Dinh Xuan Thanh, Nguyen Dinh Nguyen, Vu Van Phai, Holocene sedimentary evolution, geodynamic and anthropogenic control of the Balat river mouth formation (Red River-delta, northern Vietnam), Z. geol. Wiss., Berlin 30, 3 (2002) 157-172. [10] Vũ Quang Lân, Các mặt cắt địa chất chủ yếu của hệ tầng Hải Hưng vùng đồng bằng Sông Hồng. Tạp chí địa chất A (251) (1999) 9-13. [11] Nguyễn Quang Miên, Lê Khánh Phồn, Some results of C14 dating in investigation on Quaternary geology and geomorphology in Nam Định - Ninh Bình area, Việt Nam. Tạp chí địa chất B (15) (2000) 106-109. [12] Vũ Nhật Thắng, Phạm Đình Xin, Địa chất và Khoáng sản vùng Thái Bình – Nam Định (giới thiệu kết quả đo vẽ BDĐC và TNKS tỉ lệ 1/50.000 nhóm tờ Thái Bình – Nam Định, 1997. [13] Trần Đức Thạnh, Nguyễn Hữu Cử, Nguyễn Đức Cự, và nnk, Tình trạng và nguyên nhân xói lở, bồi tụ ven bờ châu thổ sông Hồng, Tuyển tập Tài nguyên và Môi trường biển. Tập III, Nhà xuất bản Khoa học và Kỹ thuật, Hà Nội, 2000. [14] Trần Đức Thạnh, Đinh Văn Huy, Trần Đình Lân, Đặc điểm phát triển của vùng đất bồi ngập triều ven bờ châu thổ Sông Hồng. Tạp chí Các Khoa học về Trái đất 1 (18) (1996) 50-60. [15] Ngô Quang Toàn, Đặc điểm trầm tích và lịch sử phát triển các thành tạo Đệ tứ ở phần đông bắc đồng bằng Sông Hồng, Luận án TS Khoa học Địa lí – Địa chất; Đại học Tổng hợp Hà Nội, 1995. [16] Trần Nghi, Đinh Xuân Thành và nnk, Quá trình tích tụ trầm tích Đệ tứ của đáy Sông Hồng trong mối quan hệ với hoạt động nhân sinh, Tuyển tập báo cáo hội thảo khoa học đánh giá tác động của quá trình xói mòn tại lưu vực Sông Hồng, Hà Nội, (2000) 124-151.